Odpowiedzi

2009-12-17T18:27:04+01:00
A)
2x-3y=7 |*3
3x-5y=11 |*(-2)

6x-9y=21
-6x+10y=-22
--------------------
y=1

2x-3=7
y=1

x=5
y=1

b)
5p-2r=21 |*3
3p+5r=-6 |*-5)

15p-6r=63
-15p-25r=30
--------------------
-31r=93 |: (-31)
r=3

3p+15=-6
r=3

p=-7
r=3

c)
2x-3y=10 |*5
5x+5y=0 |*(-2)

10x-15y=50
-10x-10y=0
-----------------
-25y=50|:(-25)
y=-2

2x+6=10
y=-2

x=2
y=-2

d)
5v+4w=4
7v+5v=6

5v+4w=4 |*13
13v=6 |*(-5)

65v+52w=52
-65v=-30
--------------
52w=22 |:52
w=0,42

5v+1,68=4
w=0,42

v=0,46
w=0,42


e)
4x+5y=12,3 |*2
3x-2y=-4 |*5

8x+10y=24,6
15x-10y=-20
-------------------
23x=4,6 |:23
x=0,2

0,8+5y=12,3
x=0,2

y=2,3
x=0,2
1 1 1